Freshwater chlorophycean algae from the Beaufort, Laptev and Kara Seas (Arctic Ocean) as indicators of river runoff. - Matthiessen, Jens (PANGAEA, 2000)
Freshwater chlorophycean algae are characteristic organic-walled microfossils in recent coastal and shelf sediments from the Beaufort, Laptev and Kara seas (Arctic Ocean). The persistent occurrence of the chlorophycean algae Pediastrum spp. and Botryococcus cf. braunii in marine palynomorph assemblages is related to the discharge of freshwater and suspended matter from the large Siberian and North American rivers into the Arctic shelf seas. The distribution patterns of these algae in the marine environments reflect the predominant deposition of riverine sediments and organic matter along the salinity gradient from the outer estuaries and prodeltas to the shelf break. Sedimentary processes overprint the primary distribution of these algae. Resuspension of sediments by waves and bottom currents may transport sediments in the bottom nepheloid layer along the submarine channels to the shelf break. Bottom sediments and microfossils may be incorporated into sea ice during freeze-up in autumn and winter leading to an export from the shelves into the deep sea. The presence of these freshwater algae in sea-ice and bottom sediments in the central Arctic Ocean confirm that transport in sea ice is an important process which leads to a redistribution of shallow water microfossils.
Palynology from surface sediment samples of the Arctic Ocean
Keywords: Akademik Boris Petrov; AWI_Paleo; Botryococcus per unit mass; BP97; BP97-10; BP97-12; BP97-17; BP97-19; BP97-21; BP97-27; BP97-32; BP97-35; BP97-39; BP97-42; BP97-43; BP97-46; BP97-47; BP97-48; BP97-49; BP97-50; BP97-52; BP97-55; BP97-56; BP97-58; Counting, palynology; DEPTH, sediment/rock; Desmidiaceae per unit mass; Dinoflagellate cyst per unit mass; DIVERSE; Kara Sea; KaraSea97; MULT; Paleoenvironmental Reconstructions from Marine Sediments @ AWI; Pediastrum; Pollen per unit sediment mass; Sampling gear, diverse; Siberian River Run-Off; SIRRO